2018
DOI: 10.3389/fpls.2018.01579
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Synergistic Toxicity of Terpenes as Insecticides: Contribution of Metabolic Detoxification in Musca domestica

Abstract: Essential oils, which are mixtures of terpenes, frequently show stronger insecticide activity, i.e., lower lethal dose 50 (LC50), than their most abundant terpenes. Synergy between terpenes provides a plausible explanation, but its demonstration has been elusive. In the present work, we look for an alternative explanation, by considering the influence of insect metabolic detoxification. Basically, we propose a model (metabolic model, MM) in which the LC50 of the major terpene in a mixture is expected to includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 42 publications
(58 reference statements)
1
40
1
Order By: Relevance
“…The observed larvicidal activities of C. citrinus fruit essential oil is apparently due to synergistic activities involving minor components. It has been shown that Musca domestica preferentially metabolizes the major components in an essential oil, which leaves the components of lower concentrations to act as the toxic agents [56]. Baeckea frutescens and Callistemon citrinus leaf essential oils were relatively inactive against Cx.…”
Section: Mosquito Larvicidal Activitymentioning
confidence: 99%
“…The observed larvicidal activities of C. citrinus fruit essential oil is apparently due to synergistic activities involving minor components. It has been shown that Musca domestica preferentially metabolizes the major components in an essential oil, which leaves the components of lower concentrations to act as the toxic agents [56]. Baeckea frutescens and Callistemon citrinus leaf essential oils were relatively inactive against Cx.…”
Section: Mosquito Larvicidal Activitymentioning
confidence: 99%
“…Further, the synergistic effect of the essential oil constituents likely increases their larvicidal activity [31][32][33]. Scalerandi et al proposed an interesting mode for synergistic effects using the metabolic model [34]. They have shown that while the major component in the mixture is targeted by the detoxification system of the insect, the minor component intoxicates the insect.…”
Section: Chemical Composition Of Essential Oilsmentioning
confidence: 99%
“…Several reports confirmed this synergistic effects of the oxygenated terpenes in other plants. [12,35,36]…”
Section: Antioxidant Activity Of the Vosmentioning
confidence: 99%